Phycoremediation of Precious Metals by Cladophora fracta From Mine Gallery Waters Causing Environmental Contamination - Topal, Murat; Obek, Erdal; Topal, E. Isil Arslan (Springer, 2020)
We have presented a study to determine the possibility for the usage of Cladophora fracta as bioaccumulator of the metals (Au) and silver (Ag) both have characteristics of pollutant and precious in mine water. The highest concentrations accumulated by C. fracta were determined as 5.8 +/- 0.3 and 5323 +/- 75 mu g/kg for Au and Ag, respectively. The results showed that the accumulation of the metals measured followed the order of Ag > Au. The Metal Pollution Index (MPI) values calculated between 39.37 x 10(-3) and 175.7 x 10(-3) were used to determine the pollution degree of C. fracta. As a result, it was determined that C. fracta highly accumulated the precious metals from the gallery water. Therefore, C. fracta was a good bioaccumulator for the remediation of Au and Ag in mine gallery waters. In this way, it is possible to minimize or eliminate the environmental risks of the precious metals in the gallery waters.
Keywords: Accumulation; Gallery water; Remediation; Precious metals; Contamination